Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
DOI: 10.31274/rtd-180813-15272
|View full text |Cite
|
Sign up to set email alerts
|

Use of insect pathogen Bacillus thuringiensis for control of grubs (Coleoptera: Scarabaeidae) in turf

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print cotored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
(91 reference statements)
0
3
1
Order By: Relevance
“…B. thuringiensis subspecies japonensis Buibui strain was evaluated in 1996 only and provided inconsistent control of Japanese beetle larvae (0 Ð75%). This is in contrast to the results found in a turf environment (Alm et al 1997, Michaels 2000, which showed generally higher levels of control.…”
Section: Discussioncontrasting
confidence: 86%
“…B. thuringiensis subspecies japonensis Buibui strain was evaluated in 1996 only and provided inconsistent control of Japanese beetle larvae (0 Ð75%). This is in contrast to the results found in a turf environment (Alm et al 1997, Michaels 2000, which showed generally higher levels of control.…”
Section: Discussioncontrasting
confidence: 86%
“…Suzuki et al (1992Suzuki et al ( , 1993 found the LC 50 value for Þrst-instar A. cuprea to be Ϸ0.1 g/g compost. Michaels (2000) found the LC 50 value for southern masked chafers, C. lurida, to be 5 g toxin/g root mix for third instars, Suzuki et al 1992 found the LC 50 value for A. rufocuprea to be 25 g toxin/g compost, and Koppenhofer and Kaya 1997 found the LC 50 values for the masked chafers C. hirta LeConte and C. pasadenae Casey to be 35 and 25 g toxin/g soil, respectively. Suzuki et al (1992) showed that 25 g of toxin was not effective against second-instar Allomyrina dichotoma L. (subfamily Dynastinae).…”
Section: Discussionmentioning
confidence: 97%
“…Suzuki et al (1992) showed that 25 g of toxin was not effective against second-instar Allomyrina dichotoma L. (subfamily Dynastinae). From the data presented in here and in Michaels (2000), Suzuki et al (1992Suzuki et al ( , 1993, and Bixby et al (2007), it seems that members of the subfamilies Rutelinae and Cetoniinae may be the most susceptible, followed by Dynastinae and Melolonthinae. It is important to note that the bioassay method (per os, compost, soil [autoclaved, nonautorclaved], root mix) has a profound effect on the LC 50 .…”
Section: Discussionmentioning
confidence: 81%
“…Suzuki et al (1992Suzuki et al ( , 1993 found the LC 50 for Þrst-instar A. cuprea to be Ϸ0.1 g per g compost. Michaels (2000) found the LC 50 for Cyclocephala lurida Bland, to be 5 g toxin per g root mix for third instars, Suzuki et al (1992) found the LC 50 for the A. rufocuprea, to be 25 g toxin per g compost, and Koppenhofer and Kaya (1997) found the LC 50 values for Cyclocephala hirta LeConte and Cyclocephala pasadenae (Casey) to be 35 and 25 g toxin per g soil, respectively. Suzuki et al (1992) showed that 25 g of toxin was not effective against second-instar Allomyrina dichotoma L. (subfamily Dynastinae).…”
Section: Discussionmentioning
confidence: 97%